Electrical characterization of photovoltaic cell with low‐concentration ratio square aperture concentrator. (17th August 2017) - Algareu, A. O.; Mahmoud, S.; Al‐Dadah, R. K.
Summary: Improving photovoltaic (PV) system power output is the main target of research in this field. Using concentrators with PV systems should increase the power output and consequently reduce the power production costs. However, using concentrators with PV (CPV) system has a drawback of a higher PV system temperature, which affects the voltage produced by the system leading to lower overall system power output. This paper experimentally investigates the performance of a polycrystalline silicon PV cell with a low‐concentration ratio square aperture concentrator. A 50 × 50 mm cell was tested without concentration and with a range of geometric concentration ratios (GCRs) of 4, 6, 8, and 10. Various cooling methods were studied, including no cooling, passive cooling by using finned heatsink, and active cooling by using finned heatsink and a fan, and the CPV performance was presented in conversion efficiency, the electrical power gain, and the reduction in PV material at various testing conditions. Significant improvement was obtained by using square aperture concentrator at different GCRs with highest power gain of 362.85%, PV cell material reduction of 78.39%, and efficiency increase by 72% at GCR 10 and active cooling. The results do not consider the power needed to extract the heat generated by the concentration and reduce the cell temperature by using air cooling. But the extracted heat enhances the CPV system output if it is harnessed in domestic applications such as water heating applications. These results highlight the potential of the developed CPV system.